Curative Da’wah as Psychospiritual Intervention: An Islamic Spirituality-Based Approach to Drug Addiction Rehabilitation in Indonesia - Hadi Setiawan, Ahmad (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study examines the role of curative da'wah as a psychospiritual intervention in the rehabilitation of drug addicts within an Islamic spirituality-based framework. While drug abuse in Indonesia is increasing, little research has explored how da'wah, traditionally associated with religious preaching, can be adapted into a therapeutic approach addressing the spiritual and psychosocial needs of recovering addicts. The research was conducted at the House of Serenity Rehabilitation Center in Bandar Lampung using a descriptive qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving 15 participants, including former addicts, spiritual mentors, and program managers. The analysis, guided by the Miles & Huberman interactive model, revealed three main findings: (1) structured curative da'wah sessions combining ritual, reflection, and mentoring; (2) significant changes in participants' spiritual orientation and interpersonal relationships, with 80% reporting stronger meaning in life and no relapse during the study period; and (3) empathetic communication that fosters trust, emotional resilience, and identity reconstruction. These results suggest that curative da'wah can serve as a complementary, context-specific strategy for holistic addiction recovery, with potential application in community-based and spiritually grounded mental health programs.